National Legislative Strategies for Strengthening Corporate Accountability for Environmental Damage and Social Justice in Industrial Pollution - Satriya Nugraha; Retno Saraswasti; Nikmah Fitriah (Green Social: International Journal of Law and Civil Affairs, 2025)
This study examines the effectiveness of national legislative strategies in promoting corporate accountability for industrial pollution and social justice violations. It analyzes a comparative legal framework, focusing on laws, enforcement mechanisms, and corporate liability regimes in countries such as France, Germany, Norway, China, and Australia. The research evaluates how mandatory due diligence laws, judicial measures, and transparency mechanisms help hold corporations accountable for environmental impacts. It compares voluntary compliance models with mandatory legal frameworks, noting the limitations of voluntary agreements in driving substantial environmental changes. Findings show that countries with strong legal frameworks, like the EU and Australia, achieve higher corporate compliance and environmental performance, while voluntary measures struggle to produce meaningful results. The study emphasizes the need for stronger enforcement, higher penalties for violations, and enhanced public transparency. Additionally, it explores integrating environmental justice considerations, such as community participation and fair compensation, into national strategies. The study offers policy recommendations for improving corporate responsibility through better legislation, harmonizing laws across jurisdictions, and fostering collaboration among governments, corporations, and civil society. It also suggests future research directions, including examining the long-term impacts of environmental justice policies in different global contexts.